Factors associated with development of retinopathy in patients with type 2 diabetes mellitus at onset and within three years after diagnosis - Kajsa Andersson; Anders Halling; Björn Agvall (Taylor & Francis Group, 2024)
Objective To investigate the prevalence of diabetes retinopathy and evaluate the factors influencing its occurrence both at the onset of type 2 diabetes (T2D) and three years into its duration.Design Retrospective population-based study.Setting Data was retrieved from Regional Healthcare Information Platform in Region Halland 2016-2020.Subjects Patients 35-75 years old in Region Halland receiving first-time diabetes diagnosis according to ICD-code E11-14 in 2016-17. The total cohort consisted of 1659 patients.Main outcome measures The main outcome measure of the study was the occurrence of diabetes retinopathy at onset and within three years from the diabetes diagnosis. Multivariate logistic regression analysis was conducted for diabetes retinopathy at onset and within three years, adjusted for age, gender, comorbidities, levels of HbA1c, cholesterol, kidney functional and blood pressure.Results At onset, there were 12% with diabetes retinopathy and after three years, 32% of the patients had developed diabetes retinopathy. In the study cohort, 71 of patients who were examined with fundus photography within three years after onset, and 8% had had dietary recommendation without pharmacotherapy. High HbA1c levels, blood pressure values and impaired renal function already at onset were associated with development of diabetes retinopathy at onset and this association persisted after three years. The odds ratio for diabetes retinopathy was increased adjusted for HbA1c elevations, renal impairment, and increased blood pressure at index and when adjusted for these variables three years from index.Conclusion These findings indicate that the risk of developing diabetes retinopathy is present early on at onset and within the first three years of diabetes diagnosis. This highlights the importance of promptly regulating glucose- and blood-pressure levels and follow up kidney dysfunction to mitigate the risk of diabetes retinopathy.